2009
DOI: 10.1128/jvi.01201-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chaperone BiP Interacts with Borna Disease Virus Glycoprotein at the Cell Surface

Abstract: Borna disease virus (BDV) is characterized by highly neurotropic infection. BDV enters its target cells using virus surface glycoprotein (G), but the cellular molecules mediating this process remain to be elucidated. We demonstrate here that the N-terminal product of G, GP1, interacts with the 78-kDa chaperone protein BiP. BiP was found at the surface of BDV-permissive cells, and anti-BiP antibody reduced BDV infection as well as GP1 binding to the cell surface. We also reveal that BiP localizes at the synapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…GRP78 is known to be an ER-resident chaperone protein but has also been reported to be present on the plasma membranes of several cell types, including neurons (22)(23)(24)(25)(26)(27)30). For GRP78 to be involved in JEV entry, it must be located on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GRP78 is known to be an ER-resident chaperone protein but has also been reported to be present on the plasma membranes of several cell types, including neurons (22)(23)(24)(25)(26)(27)30). For GRP78 to be involved in JEV entry, it must be located on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…GRP78 levels on the plasma membrane are generally considered to be low under normal physiological conditions, with increased levels seen in cancer cells and under conditions of cellular stress. However, several studies have shown that GRP78 is copiously localized under normal conditions on the plasma membrane in different cell types, including endothelial cells, monocytes, and neurons, carrying out varied functions (22)(23)(24)(25)(26)(27)30). GRP78 on the plasma membrane functions as a cell surface signaling receptor for activated ␣2-macroglobulin (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G ORF of BDV encodes an envelope glycoprotein, which overlaps with the upstream M ORF and contains a long intron of a 1,293 nt for expression of the downstream L gene (7,31,32). The G precursor protein, GP, plays a key role in BDV entry into susceptible cells, and the GP1, the N-terminal subunit of GP, is known to be required for receptor recognition and virus entry (14,15,16,19,22). Previous studies suggested that the expression and correct processing of BDV GP are necessary for BDV dissemination in primary cultures of neurons and that neutralizing antibodies against BDV GP completely inhibited virus spread (3).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, M also associates with vRNP in the host cell nucleus, suggesting that M is involved in viral replication or transport of viral components [15]. G is the viral envelope glycoprotein and is involved in BDV entry, involving virion attachment to an unknown receptor and fusion of the viral envelope and cell membrane to release the vRNP into the cell cytoplasm in association with host factors [16][17][18][19][20][21]. X is a multifunctional, non-structural protein that is essential for the viral replication cycle [22], and is known to be a regulator of viral polymerase activity and an inhibitor of apoptosis in the central nervous system [23 -25].…”
mentioning
confidence: 99%